Cento de Estudios - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: La Facultad de Agronomía, de la Universidad Nacional de la Amazonía Peruana, presenta en su estructura organizativa, sus centros de producción, sus investigaciones, buscando llegar a la comunidad mundial. Ubicado en Puerto Almendra, del caserio de Zungarococha
ENGLISH: The Faculty of Agronomy, of the National University of the Peruvian Amazon, presents in its organizational structure, its production centers, its research, seeking to reach the world community. Located in Puerto Almendra, in the hamlet of Zungarococha.

SPANISH: La Facultad de Agronomía, de la Universidad Nacional de la Amazonía Peruana, presenta en su estructura organizativa, sus centros de producción, sus investigaciones, buscando llegar a la comunidad mundial. Ubicado en Puerto Almendra, del caserio de Zungarococha
ENGLISH: The Faculty of Agronomy, of the National University of the Peruvian Amazon, presents in its organizational structure, its production centers, its research, seeking to reach the world community. Located in Puerto Almendra, in the hamlet of Zungarococha.
Center of Studies
Keywords: Iquitos (Perú)|~|University study centers|~|Centro de Estudio|~|Universidad|~|Iquitos (Perú)